Pelatihan Praktis Tazhiyul Mayit di Desa Pastap Julu Bersama Anak Madrasah GUPPI Sebagai Upaya Edukasi dan Pembinaan Keagamaan - Mutiah; Siti Hawa Lbs; Wildanul Husna; Nurul Sakinah; Nur Azizah Nst; Suaimah; Inri Atikah Rahmadani Lubis; Abbas Hambali; Suhdi Ansah Batubara; Lukman Nur Hakim; Elva Mahmudi (MADANI PUBLISHER INDONESIA, 2025)
In this tajhizul mayit training activity for the MDA GUPPI children of Pastap Julu Village, the community service provided guidance on important issues related to human relations with other humans, namely the problem of tajhizul mayit (corpse care). Islam pays very serious attention to this issue, so that this is one of the obligations that must be fulfilled by humanity, especially Muslims. This community service work aims to 1). Equip MDA children with tajhizul mayit skills. 2). Train MDA children to be able to implement and develop the religious knowledge they have obtained in society. Meanwhile, the benefits that will be generated from this training are 1). Improving the skills of MDA children in properly and correctly handling corpses in accordance with the teachings of Islamic law, so that if one day they are needed they are ready to use. 2). Increasing skilled personnel in handling corpses. 3). Increasing the skills of the modin in handling corpses. The result of this community service work is that the MDA GUPPI children of Pastap Julu Village have been able to implement and practice how to properly and correctly handle corpses in accordance with the provisions of Islamic law.